2002
DOI: 10.1093/jnci/94.6.437
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Intake and Risk of Colon Cancer in Women and Men

Abstract: Higher calcium intake is associated with a reduced risk of distal colon cancer. The observed risk pattern was consistent with a threshold effect, suggesting that calcium intake beyond moderate levels may not be associated with a further risk reduction. Future investigations on this association should concentrate on specific cancer subsites and on the dose-response relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
248
3
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 328 publications
(267 citation statements)
references
References 56 publications
9
248
3
7
Order By: Relevance
“…In the Cancer Prevention Study II Nutrition cohort, 9 the protective effect of total calcium was associated with intakes of over 1,255 mg/day compared to those of below 561 mg/day. The analysis of the NHS and HPFS data, 11 both of which had an interquintile range of the same magnitude (<500 mg to >1,250 mg/day), also found a protective effect of calcium on distal cancer risk. In contrast, no calcium effect was found in the Finnish study, where calcium intake was high (bottom quartile <1,178 mg).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…In the Cancer Prevention Study II Nutrition cohort, 9 the protective effect of total calcium was associated with intakes of over 1,255 mg/day compared to those of below 561 mg/day. The analysis of the NHS and HPFS data, 11 both of which had an interquintile range of the same magnitude (<500 mg to >1,250 mg/day), also found a protective effect of calcium on distal cancer risk. In contrast, no calcium effect was found in the Finnish study, where calcium intake was high (bottom quartile <1,178 mg).…”
Section: Discussionmentioning
confidence: 81%
“…9 A recent pooled analysis 12 of 10 cohort studies (not including the CPSN cohort) found a significant protective effect of calcium on colorectal cancer risk. Three case-control studies, 10,25,26 but not a fourth, 27 found similar results, but 2 cohort studies 11,28 failed to confirm them. Few studies have reported results on the association between calcium and risk of colorectal adenoma.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…[6][7][8][9] Ecological studies correlating sunlight exposure with cancer incidence provided the first evidence that vitamin D levels are inversely related to CRC development in humans. 10 Subsequent epidemiological studies have reported lower risks of CRA and CRC in individuals with high intakes and circulating levels of vitamin D. [11][12][13][14] Vitamin D plays a crucial role in calcium metabolism, and there is experimental, 15,16 epidemiologic [17][18][19] and clinical trial 20,21 data indicating that high calcium intake may also lower colorectal neoplasia risk. Furthermore, there is evidence that vitamin D and calcium may act together to reduce CRA recurrence.…”
mentioning
confidence: 99%